Sumber Daya Proyek Konstruksi Patimban Port Development Project yang Mempengaruhi Kinerja Kontraktor - Khoirina Putri Izza Rohmah; R. Machmud Sugandi; Imam Alfianto (Universitas Islam 45, 2023)
Construction project resources are one of the essential things in a construction phase. Every year, contractor performance decreases due to limitations in managing and managing project resources. One way contractors can deal with these problems is to improve quality performance during construction. One of the causes of problems at work is the resource factor. The resource factor in the construction process dramatically influences the contractor's performance. This study aims to analyze how much influence each factor of project resources (human resources, materials, equipment, implementation methods and information technology) of the project has Connecting Bridge, Patimban Port Development Project. The study collected sample data on 33 people involved in the project development process analysis using SEM-PLS analysis with the help of SmartPLS 3.0. From testing, this study's results indicate a positive and significant influence between the variables of human resources, materials, equipment amd implementation methods. This study's results obtained from the R square for the contractor performance variable were 0.809. It means that the percentage of human, material, equipment, implementation methods and information technology resources is 80.9%, while other factors influence the remaining 19.1%.